Resepsi dan Transformasi Narasi Serat Menak Yasadipuran dalam Penciptaan Wayang Menak Gaya Surakarta - Wiratama, Rudy (Perpustakaan Nasional RI, 2024)
Serat Menak is a grand corpus of Javanese-Islamic text that is adopted from the Islamic epoch, Qissa-I Emir Hamza or Hikayat Amir Hamzah, which has widely spread in Asian region in the middle of second millenium CE. The popularity of Serat Menak made this text has many variants, and the one which is largely recognized was Yasadipura I (1729-1803)'s version which was composed in the beginning of Surakarta era. The text of Serat Menak Yasadipuran then become very well-known in Java, and became the inspiration for some branches of performing arts, such as wayang, whether in its kulit, golek, krucil, or wong formats. One of these wayang genres that took its repertoire from Menak tales was wayang kulit menak, which was introduced in Surakarta in the first quarter of 20th century, the creation of Sutarja Truna Dipa (STD) which has not being scientifically studied yet until this present day. This article aims to identify how far was the relation between STD's Surakarta wayang kulit menak with Serat Menak Yasadipuran, using Wolfgang Iser's Rezeption Aesthetic approach to obtain the reception and transformation patterns from textual narratives to visual forms. The result of this research concluded that STD's Surakarta wayang menak was a living artwork which evolving along times. On the other side, STD as the implied reader has been consistent in recepting Serat Menak Yasadipuran with some additions and adaptations, which was done to fulfil the needs of performance. Innovations done by STD to his wayang menak creation were not limited in the term of transformation from textual to visual media, but also filling the gaps (leerstellen) with the rich formal interpretation, which are completing the narrative of Serat Menak, so it will be more interesting to be played.